Makna Simbolis Benih Padi dalam Cerpen “Menghantar Benih Padi Terakhir Ke Ladang” Karya Silvester Petara Hurit (International Forum of Researchers and Lecturers, 2025)
This study aims to describe the symbolism of rice seeds in the short story Sending the Last Rice Seeds to the Fields by Silvester Petara Hurit which reveals the relationship between various aspects of life and culture of the Lamaholot community, ranging from beliefs, traditions, to the relationship between humans and nature. This study uses a qualitative research method. The findings and discussion of the symbolism of rice seeds in the short story Sending the Last Rice Seeds to the Fields by Silvester Petara Hurit can be concluded as follows, 1) rice seeds as a symbol of life and fertility, 2) rice seeds as a symbol of Lamaholot tradition and culture, 3) rice seeds as a symbol of the relationship between humans and nature, and 4) rice seeds as a symbol of cultural resilience.